"إدارة الجودة الشاملة وعلاقتها بالإبداع الوظيفي دراسة تطبيقية على كلية الاقتصاد الخمس"ـ جامعة المرقب (Comprehensive Journal of Science, 2026)
Total Quality Management (TQM) is a management philosophythat strives to make the best use of all available resources and opportunities through specific improvement methods. For this reason, TQM forms the core strategy for business improvement. Functional creativity is also important for all organizations facing a changing competitive environment, and encouraging and promoting it has become a primary objective for many organizations. The importance of creativity has increased with the intensification of competition between organizations, especially international competition, which has increased the organization's need for creativity to avoid the risk of decline and extinction. This study aimed to identify the level of TQM practices in institutions and to determine whether there is a statistically significant effect ofprocess management, employee relations, and customer relations on functional creativity to achieve the study's objectives, the descriptive and analytical approaches, as well as a field survey, were used to collect data using the study instrument and analyze it statistically toanswer the questions and test the validity of the hypotheses. Through the results of the statistical analysis and Pearson's correlation test, it was found that there is a relationship between the dimensions of the internal audit quality variable (continuousimprovement, student focus, employee participation) and job creativity. Continuous improvement facilitates communication between the college's departments to implement total quality management. Among the study's findings, the college's departmentsuse the results of administrative performance evaluation in continuous improvement procedures. The college also maintains the practice of holding seminars and lectures to emphasize the concept of total quality management. The college is keen on training and developing employees in the field of total quality management. Moreover, the required tasks are completed on time and appropriately with minimal errors. The researcher recommended the necessity of emphasizingthe independence of internal auditors from any external influences, whether administrative or political. Internal auditors should report directly to the audit committee or the board of directors instead of following the daily operations management. To ensure that auditors possess the necessary skills and knowledge to identify gaps and improve organizational performance, continuous training programs should be provided that keep pace with the latest trends and techniques in auditing.
Keywords: Quality. Total Quality Management. Job Creativity